(untitled) (Sains Humanika, 2023)
The aim of this study is to develop Microbit Basic Module Teaching Aids to be used in learning electronic design, RBT level 2 subject. Specifically, the objective of this study is to identify the essential elements to produce the Microbit basic module and develop the module to determine its usability. Furthermore, it is conducted using the learning theory of cognitivism and is developed based on the Addie model. This study will involve three expert parties: one daily high school design and technology subject teacher and two Sultan Idris University of Education lecturers in the engineering field to be interviewed and gain insight into the Microbit Basic Module Teaching Aids to be developed. As for the research instrument, this study will use an inventory of interview protocols with experts who have been appointed. The findings of the study show that this developed PDP module needs improvements that several experts will suggest. As soon as these teaching aids are available, they are expected to help improve achievement and understanding and serve as an additional reference for students.